1975
DOI: 10.1063/1.431157
|View full text |Cite
|
Sign up to set email alerts
|

Elastic scattering of 13 to 100 eV electrons from N2

Abstract: The cross section for elastic scattering of electrons from N2 has been measured between 13 and 100 eV. The relative differential cross sections for elastic scattering and for excitation of the C 3Il. v' = 0 and I bands were measured over the angular range from 20· to 90· in the 13-35 eV region and from 5· to 90· in the 40-100 eV region. The integrated cross sections were placed on an absolute basis by normalizing the C 3Il. v' = 0 excitation cross section to the known emission cross section for the Second Posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Inner atoms of the molecule are screened by the outer atoms which do not contribute to the scattering, thereby causing the lessening of the cross-section. In Figures 8(b ,c), we present IECS and MTCS, respectively, along with the experimental data [4,[9][10][11][12]22,34] and theoretical calculations [29,31,32]. In both cases, our calculations show good agreement with the experimental observations above 10 eV.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Inner atoms of the molecule are screened by the outer atoms which do not contribute to the scattering, thereby causing the lessening of the cross-section. In Figures 8(b ,c), we present IECS and MTCS, respectively, along with the experimental data [4,[9][10][11][12]22,34] and theoretical calculations [29,31,32]. In both cases, our calculations show good agreement with the experimental observations above 10 eV.…”
Section: Resultssupporting
confidence: 70%
“…TCS data for both electron and positron scattering have been measured by Hoffman et al [21]. IECS measurements have been reported by Finn and Doering [22]. Furthermore, Itikawa [4], Shyn and Carignan [9] and Srivastava et al [10] reported data on IECS and MTCS.…”
Section: Introductionmentioning
confidence: 92%
“…In figures 1, 2 and 3 we compare our calculated cross sections for N 2 with experimental data from [14][15][16] and find a general good agreement. Figure 4 shows the integral elastic Integral elastic cross section for N 2 .…”
Section: Resultssupporting
confidence: 56%
“…Figure 4 shows the integral elastic Integral elastic cross section for N 2 . Solid curve: our results; squares: experimental results from [14]; circles: experimental results from [15]; diamonds: experimental results from [16].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the set of cross sections was used that was proposed in [23] and obtained on the basis of mea surements of the total and differential [24,27] cross sections of scattering and also on the ground of theo retical calculations [28,29]. Additional normalization of the set of cross sections with respect to experimental data (transfer coefficients and the Townsend coeffi cient) was not conducted; however, the comparison of the drift velocity and the characteristic energy of elec trons calculated on the basis of this set of cross sections ( ) ( )…”
Section: Solving the Kinetic Boltzmann Equation For Eedfmentioning
confidence: 99%